Pond fertilization through inorganic sources: an overview - Das, S K; Jana, B B (Indian Journal of Fisheries, 2011)
Input of nutrients through inorganic sources has long been a common practiceof pond fertilization. The state of the art of pond fertilization has been reviewedin the present paper. Phosphorus through phosphate fertilizer is the mostimportant nutrient regulating the productivity offish ponds as 1 kg P2Os wentinto 2.5 to 28.22 kg of carp production under different conditions. In most cases,nitrogen is not considered as a limiting nutrient of pond productivity. Nitrogenmay be eliminated from fertilization programme in case of old well fertilisedponds without reducing fish yields, however, there are differences of opinionregarding the importance of nitrogen fertilizer in fish ponds. The ratio of Nand P seems to play an important role in limiting the efficacy of nitrogenfertilizers. P limitation of phytoplankton occurs when the N : P ratio of thenutrient supply is substantially higher than the mean atomic ratio of N to Pin phytoplan kton cells (15 : 1); an ambient ratio less than 15 : 1 results inN limitation. The role of potassium as fertilizer in the pond culture systemhas not been properly assessed. As fish pond soils exhibit higher amount oforganic mattsr than upland agricultural soils and as the pH of bottom soiland water remains alkaline, availability of potassium in the pond sedimentis high. Thus, the concept of pond fertilization should be based on NPC ratherthan NPK as practised in agricultural soil with less organic matter.Generalised schedule of pond fertilization resulted in high variability ofproductivity in different agroclimatic areas. Many interacting factors such assoil type, wa;er depth, water retention time, species of culture, quality andquantity of vegetation should be taken into consideration. More studies onpond fertilization in the context of nutrient dynamics and fertilizer-microbialinteractions under different agroclimatic regions are necessary for an effective,appropriate and economic fertilization programme. Also, the environmentalconsequences of overfertilization resulting in pollution and subsequent hazardsin public health should be taken into account.